2020
DOI: 10.3390/clockssleep2020010
|View full text |Cite
|
Sign up to set email alerts
|

Global Research Output on Sleep Research in Athletes from 1966 to 2019: A Bibliometric Analysis

Abstract: This study examined sleep research in athletes published between 1966 and 2019, through a bibliometric analysis of research output in the Scopus database. Following a robust assessment of titles, the bibliometric indicators of productivity for studies included in the final analysis were: Distribution of publications and citations (excluding self-citations), top ten active journals, countries, institutions and authors, single- and multi-country collaboration, and 25 top-cited papers. Out of the 1015 papers, 313… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“… 5 , 6 For example, Sargent et al 6 demonstrated that more naps were taken on training days compared to rest days, and strategic napping during the day, as well as sleep hygiene practices (ie, healthy sleep practices) at night need to be considered. While several studies have investigated the impact of restricting or extending sleep on a number of outcomes of athletic performance (eg, sprint times, reaction time), 7 there has been comparatively less focus on the impact of napping. 8 , 9 It is possible that the lack of dedicated napping research in athletes may limit the ability of athletes, coaches and sports professionals to effectively implement strategic napping within their training programs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 6 For example, Sargent et al 6 demonstrated that more naps were taken on training days compared to rest days, and strategic napping during the day, as well as sleep hygiene practices (ie, healthy sleep practices) at night need to be considered. While several studies have investigated the impact of restricting or extending sleep on a number of outcomes of athletic performance (eg, sprint times, reaction time), 7 there has been comparatively less focus on the impact of napping. 8 , 9 It is possible that the lack of dedicated napping research in athletes may limit the ability of athletes, coaches and sports professionals to effectively implement strategic napping within their training programs.…”
Section: Introductionmentioning
confidence: 99%
“… 11 The majority of research examining athletes’ sleep has focused on the impact of night-time sleep on performance and recovery. 7 , 9 Yet, napping represents an opportunity to supplement the night-time sleep period, which may assist athletes in obtaining recommended sleep. Previous research on non-athletes has shown that napping can improve daytime sleepiness, mood and cognitive performance, 12–14 with the magnitude of these effects comparable to other sleep restriction countermeasures (eg, caffeine, modafinil).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research highly recommends further identification and treatment of common sleep disorders in elite athletes, 10,41 and underlines the importance of educating coaches and athletes regarding sleep to reduce the risk of injury in elite athletes. 42 As for sleep assessment, portable PSG is considered a promising tool in assessing athletes' sleep architecture out of the sleep laboratory and within applied settings, 20 but no studies have focused on possible negative effects of sleep quality assessment itself.…”
Section: Perspectivementioning
confidence: 99%
“…However, sleep is a rather challenging matter in elite sports (Caia et al, 2018 ; Kölling et al, 2019 ). Multiple internal and external circumstances negatively affect an athlete's sleep quality and quantity and can be determined as salient risk factors for sleep inadequacy in athletes (Kölling et al, 2016b ; Lastella et al, 2020 ; Walsh et al, 2020 ). For one thing, international air travel is required for athletes to get to different competition grounds or training camps.…”
Section: Introductionmentioning
confidence: 99%